A Whole Genome Assembly of the Horn Fly, Haematobia irritans, and Prediction of Genes with Roles in Metabolism and Sex Determination. Issue 5 (1st May 2018) - Konganti, Kranti; Guerrero, Felix D; Schilkey, Faye; Ngam, Peter; Jacobi, Jennifer L; Umale, Pooja E; Perez de Leon, Adalberto A; Threadgill, David W
Abstract: Haematobia irritans, commonly known as the horn fly, is a globally distributed blood-feeding pest of cattle that is responsible for significant economic losses to cattle producers. Chemical insecticides are the primary means for controlling this pest but problems with insecticide resistance have become common in the horn fly. To provide a foundation for identification of genomic loci for insecticide resistance and for discovery of new control technology, we report the sequencing, assembly, and annotation of the horn fly genome. The assembled genome is 1.14 Gb, comprising 76, 616 scaffolds with N50 scaffold length of 23 Kb. Using RNA-Seq data, we have predicted 34, 413 gene models of which 19, 185 have been assigned functional annotations. Comparative genomics analysis with the Dipteran flies Musca domestica L., Drosophila melanogaster, and Lucilia cuprina, show that the horn fly is most closely related to M. domestica, sharing 8, 748 orthologous clusters followed by D. melanogaster and L. cuprina, sharing 7, 582 and 7, 490 orthologous clusters respectively. We also identified a gene locus for the sodium channel protein in which mutations have been previously reported that confers target site resistance to the most common class of pesticides used in fly control. Additionally, we identified 276 genomic loci encoding members of metabolic enzyme gene families such as cytochrome P450s, esterases and glutathione S-transferases, and several genes orthologous to sex determination pathway genes in other Dipteran species.